RESPON MAHASISWA FUAD UIN MAHMUD YUNUS BATUSANGKAR DALAM MENANGGAPI KONTEN DAKWAH ISLAM DI MEDIA SOSIAL TIKTOK - Yulianti, Nur Evi; Okditazeini, Vannyora (KINEMA: Jurnal Komunikasi dan Penyiaran, 2024)
This research aims to understand how students from FUAD UIN Mahmud Yunus Batusangkar respond to Islamic dakwah content on TikTok. The theory used in this research is the S-O-R (Stimulus-Organism-Response) theory. This research uses a quantitative research methodology with a descriptive approach by using the Product Moment correlation significance test, comparing rCalculated with rTable. The data collection technique used is by distributing questionnaires to students of the Faculty of Ushuluddin, Adab, and Dakwah from the 2020, 2021, 2022, and 2023 cohorts with a total sample of 90 respondents. The research found that there is a fairly strong relationship between the dakwah content variable and the student response, where the results from the Product Moment correlation test obtained a coefficient value of 0.463, indicating a fairly strong positive relationship between the two variable values. This can also be seen from the dakwah content variable aspects of practicing faith, implementing amar makruf nahi mungkar, building an Islamic community, spreading the creed, and achieving welfare with a grand mean value of 3.46, which makes student response necessary for dakwah content on TikTok. For the student response variable aspects of attitude, opinion, behavior, cognition, affection, and conation with a grand mean value of 3.34, this makes the student response also influential in the dakwah content on TikTok. The coefficient of determination (R Square) value is 21.4%, indicating that the response of FUAD UIN Mahmud Yunus Batusangkar students to Islamic dakwah content on TikTok is 21.4. However, the unique findings in this study indicate that it turns out that FUAD students who consume Islamic preaching content on Tiktok social media are only a few or do not really respond to the preaching content.